Erratum: Subgingival chlorhexidine irrigation for scaling and root planing adjunctive therapy in chronic periodontitis: a systematic review (Faculty of Medicine Universitas Indonesia, 2023)
[This corrects the article DOI: 10.13181/mji.rev.236337]